Trois nouvelles espèces de Cucullanus (Nematoda: Cucullanidae) de poissons marins au large de la Nouvelle-Calédonie, avec une clé des espèces de Cucullanus d'Anguilliformes - Moravec, František; Justine, Jean-Lou (Parasite, 2018)
Based on light and scanning electron microscopical studies of nematode specimens from the digestive tract of some rarely collected anguilliform and perciform fishes off New Caledonia, three new species of Cucullanus Müller, 1777 (Cucullanidae) are described: C. austropacificus n. sp. from the longfin African conger Conger cinereus (Congridae), C. gymnothoracis n. sp. from the lipspot moray Gymnothorax chilospilus (Muraenidae), and C. incognitus n. sp. from the seabream Dentex fourmanoiri (Sparidae). Cucullanus austropacificus n. sp. is characterized by the presence of cervical alae, ventral sucker, alate spicules 1.30-1.65 mm long, conspicuous outgrowths of the anterior and posterior cloacal lips and by elongate-oval eggs measuring 89-108 × 48-57 μm; C. gymnothoracis n. sp. is similar to the foregoing species, but differs from it in the absence of cervical alae and the posterior cloacal outgrowth, in the shape and size of the anterior cloacal outgrowth and somewhat shorter spicules 1.12 mm long; C. incognitus n. sp. (based on female morphology) differs from other congeneric species parasitic in the Sparidae mainly in possessing cervical alae, the postequatorial vulva, phasmids situated at the mid-length of the tail and in the size of the eggs (75-84 × 45-66 μm). A key to species of Cucullanus parasitizing anguilliform fishes is provided.
Keywords: Nematode Infections; Animals; New Caledonia; Nematoda; Female; Nová Kaledonie; Eels; ženské pohlaví; Microscopy, Electron, Scanning; Perciformes; nemoci ryb; kloaka; mikroskopie elektronová rastrovací; nematodózy; Fish Diseases; gastrointestinální trakt; hlístice; Male; zvířata; mužské pohlaví; Gastrointestinal Tract; mikroskopie; Anguilliformes; Microscopy; Cloaca